(untitled) (Research, Society and Development, 2022)
The current study used the Systematic Review method with aim of raising and discussing which are the most used instruments for evaluating self-esteem in children from four to six years old, as well as identifying what types of studies were carried out with them, when they appeared and observing the countries with the highest incidence of the tests application, beyond the reality of the instruments in Brazil. Relevant articles published in the PubMed database were selected in any period and all languages. From the analysis of the studies, it was observed that there are limitations that hinds a deeper theoretical view on the topic. About the impasses, it must be highlighted the absence of studies on self-esteem for the pre-established age group and low rate of brazilian studies about this theme.